THE EFFECT OF ECONOMIC CONDITIONS AND PARENTS’ MOTIVATION ON MATHEMATICS LEARNING OUTCOMES OF HIGHGRADE STUDENTS AT SDN 04 BIAU, BUOL REGENCY - Sulastri Harun (European Journal of Humanities and Educational Advancements, 2022)
This research is based on the researcher’s thoughts on the importance of the influence of parental motivation and support for family factors to improve student achievement. In particular, the socio-economic condition of the student’s family. Parents with what kind of family economic conditions can support their children’s education as students and how parents’ economic conditions affect their motivation so that it has an impact on their children’s learning outcomes. The problem raised in this study is whether there is an influence between family socioeconomic conditions and parental motivation on high grade students’ mathematics learning outcomes at SDN 04 BIAU BUOL, Central Sulawesi. Where this problem, the researcher has three initial hypotheses that become allegations of the problem. This study aims to determine whether there is an influence of family socio-economic conditions and learning motivation on students’ mathematics learning outcomes at the school. This type of research is field research with quantitative research methods, surveys. The location of this research is SDN 04 BIAU BUOL. The object of this research is the economic condition of the parents, the motivation of the parents and the mathematics learning outcomes of high-class students. The sample in this study amounted to 42 respondents, namely students consisting of class V and VI. Collecting data in this study using questionnaires, interviews, test results (Semester Final Assessment) and documentation. Data analysis used multiple linear regression analysis techniques to see whether there was an influence between the variables of Economic Condition and Parents’ Motivation on variable Y, namely the Mathematics Learning Outcomes of High Grade Students at SDN 04 BIAU. Based on the research, it can be concluded that H1 is not proven, where there is no significant influence of parents’ economic conditions on students’ mathematics learning outcomes, this can be seen from the data processing carried out by researchers where it is known that the Sig value for the effect of X1 on Y is 0.068 > 0 .05 and t value Calculate 1.877 < t table 2.022. H2 is accepted because it is known that the Sig value for the influence of X2 on Y is 0.003 <0.05 and the tcount value is 3.223>from t table 2.022 so it can be concluded that H2 is accepted which means that there is an influence of parental motivation (X2) on student learning outcomes (Y) . And H3 which shows a significant value for the effect of X1 and X2 simultaneously on Y is equal to 0.001 <0.05 and the calculated F value is 8.376 >F table 3.23, so it can be concluded that H3 is accepted which means that there is an influence of economic conditions (X1) and parental motivation (X2) simultaneously on Y.